Rational Moralists and Moral Rationalists Value-Based Management: Model, Criterion and Validation - McCullough, P. Michael (Journal of business ethics, 2005)
This paper considers ethical decision making by blending three streams of related research: cognitive moral development of the decision maker, rational choice theory and a subjective expected utility model. Ethical dilemmas can be defined as situations where moral certainty is compromised by rational cognition. In this paper, the authors assume that some people use a morality-first perspective and others a rationality-first perspective. Ethical scenarios were written and used to test hypotheses derived from this perspective. The instrument developed was shown to be in need of further refinement. Results are discussed in terms of relationships between participant-characteristics variables overall and subscale responses to the ethical scenarios.